High-speed and potentially scalable UWOC/UWB converged transmission link for underwater wireless optical sensor networks - Armghan, Ammar; Alsharari, Meshari; Aliqab, Khaled; Alrashdi, Ibrahim; Kanwal, Benish; Mirza, Jawad; Aziz, Imran (Frontiers in Physics, 2025)
Underwater wireless optical sensor networks require high-speed, long-range, and scalable underwater wireless optical communication/ultra-wideband hybrid links to enable real-time data transmission and reliable communication between sensors and surface stations. Such hybrid links can provide seamless connectivity, adaptability to changing underwater environments, and support for various applications including ocean exploration, monitoring, and surveillance. We report an underwater wireless optical communication/ultra-wideband converged transmission link for 5×1.5 Gb/s underwater wireless optical sensor networks. The directly-modulated lasers are used to modulate and transmit the sensors’ data over underwater wireless optical communication channels towards floating optical base station having radio-access units where multiple ultra-wideband signals are generated employing optical delay line technique. Intensity modulation/direct detection scheme based upon On-off keying modulation is employed in this work. The performance of the sensors is examined taking into account various water bodies and turbulence regimes using metrics of Bit-error rate, Quality factor, and Error-vector magnitude utilizing Gamma-Gamma statistical channel model. The simulation results obtained indicate that forward-error correction target Bit-error rate of 3.8×10−3 is successfully achieved for sensors considering different water bodies and turbulence regimes. The proposed system is potentially scalable, accommodating increased sensors, and supporting higher rates while efficiently generating and processing ultra-wideband signals.